2003
DOI: 10.1046/j.1445-2197.2003.02737.x
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic cutaneous squamous cell carcinoma to the parotid: the role of surgery and adjuvant radiotherapy to achieve best outcome

Abstract: Parotid gland lymph node metastases from cutaneous squamous cell carcinoma are associated with a high rate of recurrence and cause-specific mortality despite current best practice (surgery and high dose adjuvant radiotherapy). The role of more aggressive surgery, altered fractionation or chemotherapy to enhance locoregional control remains unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
47
2
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 37 publications
7
47
2
1
Order By: Relevance
“…Despite these misgivings, previous studies have highlighted the importance of adjuvant radiotherapy in conferring better regional control and improved survival compared with either surgery alone or radiotherapy alone. [12][13][14][15][16][17] In a series of patients with metastatic cSCC to cervical lymph nodes, the 5-year disease-free survival rate was improved significantly in patients who underwent surgery and received adjuvant radiotherapy compared with patients who underwent surgery alone (73% vs 18%; P ¼ .001), and locoregional control also was improved (77% vs 15%). 14 Jol et al also reported a decreased locoregional failure rate in patients who underwent surgery and adjuvant radiotherapy compared with patients who underwent surgery alone (17% vs 44%).…”
Section: >3mentioning
confidence: 97%
See 2 more Smart Citations
“…Despite these misgivings, previous studies have highlighted the importance of adjuvant radiotherapy in conferring better regional control and improved survival compared with either surgery alone or radiotherapy alone. [12][13][14][15][16][17] In a series of patients with metastatic cSCC to cervical lymph nodes, the 5-year disease-free survival rate was improved significantly in patients who underwent surgery and received adjuvant radiotherapy compared with patients who underwent surgery alone (73% vs 18%; P ¼ .001), and locoregional control also was improved (77% vs 15%). 14 Jol et al also reported a decreased locoregional failure rate in patients who underwent surgery and adjuvant radiotherapy compared with patients who underwent surgery alone (17% vs 44%).…”
Section: >3mentioning
confidence: 97%
“…[12][13][14][15][16][17] Recurrence reflects clinical progression of residual microscopic cSCC either after surgery alone or after surgery and adjuvant radiotherapy. The objective of adjuvant radiotherapy is to decrease the risk of regional recurrence by eradicating microscopic cSCC.…”
Section: Original Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Residual microscopic disease is treated by high dose adjuvant radiotherapy. Eddy et al, recommend that the facial nerve is only sacrificed if it is grossly involved by tumor [20] .…”
Section: Discussionmentioning
confidence: 99%
“…[64][65][66][67] To date, however, no prospective study has demonstrated a survival benefit where elective neck dissection is added to management of high-risk cSCC of the head and neck in the N0 setting. 67 Studies report rates of occult nodal metastasis of 10 to 60%.…”
Section: Elective Neck Dissectionmentioning
confidence: 99%